2022
DOI: 10.3390/cells11030415
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targets in Amyotrophic Lateral Sclerosis: Focus on Ion Channels and Skeletal Muscle

Abstract: Amyotrophic Lateral Sclerosis is a neurodegenerative disease caused by progressive loss of motor neurons, which severely compromises skeletal muscle function. Evidence shows that muscle may act as a molecular powerhouse, whose final signals generate in patients a progressive loss of voluntary muscle function and weakness leading to paralysis. This pathology is the result of a complex cascade of events that involves a crosstalk among motor neurons, glia, and muscles, and evolves through the action of converging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…However, there is no ubiquitous association with any specific risk factor or molecular mechanism that forms a basis for a unifying theory of ALS/FTD ( Keon et al, 2021 ). Excitotoxicity has been hypothesized to trigger several forms of neurodegenerative disease, and it has long been considered a potential explanation for ALS, as well as providing a rationale for its mitigation by riluzole or edavorone, presently the only fully licensed treatments for ALS ( Cheah et al, 2010 ; Brooks et al, 2022 ; Sever et al, 2022 ; Tarantino et al, 2022 ). However, the potential associations between activity or excitotoxicity with ALS or FTD remain controversial ( Chiò et al, 2005 ; Huisman et al, 2013 ; Gallo et al, 2016 ; Starr and Sattler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no ubiquitous association with any specific risk factor or molecular mechanism that forms a basis for a unifying theory of ALS/FTD ( Keon et al, 2021 ). Excitotoxicity has been hypothesized to trigger several forms of neurodegenerative disease, and it has long been considered a potential explanation for ALS, as well as providing a rationale for its mitigation by riluzole or edavorone, presently the only fully licensed treatments for ALS ( Cheah et al, 2010 ; Brooks et al, 2022 ; Sever et al, 2022 ; Tarantino et al, 2022 ). However, the potential associations between activity or excitotoxicity with ALS or FTD remain controversial ( Chiò et al, 2005 ; Huisman et al, 2013 ; Gallo et al, 2016 ; Starr and Sattler, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the pharmacological treatments used in ALS are symptomatic treatments: spasticity (muscle relaxants or cannabinoids [84]), sialorrhoea (hypersalivation) (anticholinergic drugs), pain (tricyclic antidepressants, nonsteroidal anti-inflammatory drugs, opioids, and cannabis), respiratory insufficiency (noninvasive ventilation), and others [5]. In addition, great interest has been placed in research on drugs that act on ion channels and on skeletal muscle [85,86]. These authors have even established the possible relationship between ALS, muscle atrophy, and the taking of statins (atorvastatin) (drug used to lower serum cholesterol levels) [87].…”
Section: Discussionmentioning
confidence: 99%
“…Already in 2006, Kaiser and co-authors demonstrated a reduction in potassium channels in SOD1 G93A mice leading inevitably to MN death. More recently, alterations in chloride channels were associated with muscle channelopathies, atrophy, and OS [ 160 , 161 ] and the decreased expression of calcium channels in the spinal MNs of SOD1 G93A mice was correlated with excess mitochondrial calcium and the production of ROS [ 162 , 163 ].…”
Section: Oxidative Stress and Inflammation In Alsmentioning
confidence: 99%